PENGEMBANGAN VIDEO ANIMASI BERBASIS CERITA LEGENDA NUSANTARA UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK TEKS NARASI SISWA KELAS IV DI SDN 10 LANGSA - Yunda Fadilah; Juliati; Rapita Aprilia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
His research is motivated by the low listening skills of fourth-grade students at SDN 10 Langsa. This issue occurs due to the limited use of interactive and engaging learning media for students. Therefore, the purpose of this study is to create learning media tailored to student needs, test its feasibility, and ensure the effectiveness of this Legend Story Animation Video. This study employs the Research and Development (R&D) method, utilizing the ADDIE model. The research involved expert validators, including material experts, media experts, and language experts. It also involved a practitioner (teacher) and 19 fourth-grade students at SDN 10 Langsa. Data were collected through observations of Indonesian language learning, interviews with the fourth-grade teacher, expert evaluations, teacher response questionnaires, student response questionnaires, as well as pretest and posttest evaluation results. The results of this study yielded highly satisfactory outcomes, categorized as "Very Feasible" and "Very Practical". Thus, this Nusantara legend animation video is suitable for use as an Indonesian language learning medium for narrative text material in elementary schools